Establishment of the first International Standard for human anti-typhoid capsular Vi polysaccharide IgG. (November 2018) - Rijpkema, Sjoerd; Hockley, Jason; Logan, Alastair; Rigsby, Peter; Atkinson, Eleanor; Jin, Celina; Goldblatt, David; Liang, Haoyu; Bachtiar, Novilia S.; Yang, Jae Seung; Goel, Akshay; Ramasamy, Venkatesan; et al.
Abstract: Vi capsular polysaccharide (Vi) conjugate vaccines, which can prevent typhoid in infants and young children, are being developed. Comparative immunogenicity studies are facilitated by an International Standard (IS) for human anti-Vi IgG. 16/138, a pool of sera from volunteers which received either Vi conjugate vaccine or plain Vi vaccine, was assessed as an IS alongside U.S. reference reagent Vi-IgGR1, 2011 . Samples were tested in a commercial ELISA ( n  = 7), a standardised ELISA based on biotinylated Vi ( n  = 7) and in-house ELISAs ( n  = 7). Valid estimates were obtained for the potency of all samples in the commercial ELISA, and the commutability of 16/138 and Vi-IgGR1, 2011 was evident for the commercial ELISA and in-house ELISAs based on a coating of Vi and protein. The WHO Expert Committee on Biological Standardization established 16/138 as the first IS for anti-Vi IgG with 100 IU per ampoule and assigned 163 IU per vial of Vi-IgGR1, 2011 .